Book review: Roger Morriss. Science, Utility and Maritime Power: Samuel Bentham in Russia, 1779-1791. Farnham, Surrey: Ashgate, 2015. ISBN 978-14-72-41267-6. Pp. xvi, 274, 2 maps. Hardback; e-book. £70.00. Issue 5 (2015) - Lambert, Andrew
No abstract available